Stories from Japan - Dolch, Edward William 1889-1961.; Dolch, Marguerite Pierce 1891-.; Hawkinson, John 1912-.; Hawkinson, Lucy Ozone 1924-. (Champaign, Ill Garrard Press, 1960)
Twenty episodes from Japanese folklore including the well known "Momotaro, the Peach Boy" and
Keywords: Tales -- Japan; Folklore -- Japan